2022
DOI: 10.1021/acs.analchem.2c04051
|View full text |Cite
|
Sign up to set email alerts
|

DNA Computation-Modulated Self-Assembly of Stimuli-Responsive Plasmonic Nanogap Antennas for Correlated Multiplexed Molecular Imaging

Abstract: Nanogap antennas with strong electromagnetic fields of the “hot spot” in the gap region of two adjacent particles that can significantly improve the optical properties of fluorophores hold great potential for ultrasensitive bioanalysis. Herein, a DNA computation-mediated self-assembly of Au NBP dimer-based plasmonic nanogap antennas was designed for imaging of intracellular correlated dual disease biomarkers. It is worth noting that with the benefit from the electromagnetic fields of the “hot spot” in the gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…MicroRNAs (miRNAs) are endogenous short noncoding RNAs that typically comprise 20–24 nucleotides and play important roles in various biological processes within the cells. As a member of the miRNA family, miRNA-21 (miR-21) is overexpressed in many cancers and is widely used as a biomarker for early cancer screening. , Using the activator (named AS miR‑21 ) designed by the “13 + 3 RESET” effect, a CRISPR/Cas12a-based miR-21 biosensor was designed (Figure A). AS miR‑21 could efficiently activate the trans -cleavage activity of CRISPR/Cas12a, inducing a high level of fluorescence due to the enzyme-catalyzed cleavage of FQ-reporter (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous short noncoding RNAs that typically comprise 20–24 nucleotides and play important roles in various biological processes within the cells. As a member of the miRNA family, miRNA-21 (miR-21) is overexpressed in many cancers and is widely used as a biomarker for early cancer screening. , Using the activator (named AS miR‑21 ) designed by the “13 + 3 RESET” effect, a CRISPR/Cas12a-based miR-21 biosensor was designed (Figure A). AS miR‑21 could efficiently activate the trans -cleavage activity of CRISPR/Cas12a, inducing a high level of fluorescence due to the enzyme-catalyzed cleavage of FQ-reporter (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Benefitting from the controllable sensing manner, stimuli-responsive sensing probes have been exploited to regulate sensing functions by exogenous or endogenous activation for improving imaging spatial accuracy. For exogenous activation, near-infrared (NIR) light-activated signal amplification strategy has been reported for spatiotemporally controlled ultrasensitive imaging. , Despite these progresses made, tumor-specific sensing and imaging are still significantly constrained and not yet available. On the contrary, endogenous activation as the promising candidate for site-specific activation provides an alternative way to realize the tumor-specific sensing and imaging with high efficiency. , Previous studies demonstrated that endogenous apurinic/apyrimidinic endonuclease 1 (APE1) is overexpressed in the cytoplasm of tumor cells instead of normal cells. , Therefore, engineering of endogenously activated tumor-specific signal amplification strategies based on this differential expression level of APE1 is expected to reduce off-tumor signal leakage and ultimately improve the discrimination ratio of cancer/normal cells. Although endogenous activation strategies such as dual-lock strategies have been reported previously, the discrimination ratio of cancer/normal cells (∼2.6-fold) is still limited due to the lack of signal amplification in this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, endogenous activation as the promising candidate for site-specific activation provides an alternative way to realize the tumor-specific sensing and imaging with high efficiency. 25,26 Previous studies demonstrated that endogenous apurinic/apyrimidinic endonuclease 1 (APE1) is overexpressed in the cytoplasm of tumor cells instead of normal cells. 18,27 is expected to reduce off-tumor signal leakage and ultimately improve the discrimination ratio of cancer/normal cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Specific imaging of cancer cell based on biomarkers is of high significance to achieve the early cancer diagnosis and the reduction of disease related mortality. The combination of precise base-pairing, excellent biocompatibility, and the high programmability has rendered DNA circuits excellent devices for biomedical imaging in living cells. Particularly, DNA circuits that could ingeniously integrate programmable DNA self-assembly and functional modules of signal amplification have been constructed for low-abundance biomarkers imaging. As a typical isothermal DNA circuit, toehold-mediated strand displacement (TMSD) reaction has been developed for amplification detection of biomarkers of interest. , Besides, spatial-confinement effect limited the substrates into a nanoscale for high local concentration, which significantly enhanced the operating efficiency of those DNA circuits. , Based on the principle, some emerging DNA circuits, including localized TMSD circuit, were developed. , Despite the improvements in the sensitivity of these methods, cancer cell imaging specificity is still constrained, mainly owing to the signal leakages from the confined space , and the false positive associated with single-biomarker detection, because most biomarkers overexpressed in cancer cells also exist in normal cells, such as miR-21. , Accordingly, establishing multiple activation DNA circuits with specific control to achieve highly reliable cancer cell imaging is needed.…”
mentioning
confidence: 99%